Just 'nanging' around – harmful nitrous oxide use: a retrospective case series and review of Internet searches, social media posts and the coroner's database. Issue 10 (23rd May 2022) - Chiew, Angela L.; Raubenheimer, Jacques E.; Berling, Ingrid; Buckley, Nicholas A.; Becker, Therese; Chan, Betty; Brett, Jonathan
Abstract: Background: The chronic recreational inhalation of nitrous oxide (N2 O) 'nanging', can have adverse neurological and psychiatric effects. Aim: To evaluate cases of chronic N2 O use presenting to two hospitals, as well as to evaluate nationally N2 O deaths reported to the coroner and trends in Internet searches and social media posts related to N2 O. Methods: Retrospective review of two toxicology units, from July 2017 to October 2020, of patients presenting with chronic N2 O use and neurological and/or psychiatric symptoms. We evaluated 10 years (2010–2019) of Internet search and social media trends involving N2 O and the National Coronial Information System (NCIS) database for deaths across Australia. Results: Twenty‐two patients were identified: median age 22 years, half female, 17 Asian background and 15 students. Presentations included decreased mobility or unsteady gait ( n = 15) and psychiatric symptoms ( n = 5). The median reported bulb use/day was 300 (interquartile range (IQR): 200–370), for a median of 6 months (IQR: 3–24). On magnetic resonance imaging, 10/18 had subacute combined degeneration of the spinal cord and 7/7 sensorimotor neuropathy on nerve conduction studies. All received high‐dose intramuscular vitamin B12 and 11 methionine. Despite prolonged rehabilitation, nine required walking aids on discharge. Since 2017, social media posts and Internet searches for N2 O increased rapidly, the latter mostly directed at obtaining N2 O canisters. From the NCIS, 36 deaths were identified, 12 unintentional (recreational drug use), 20 intentional self‐harm and 4 traumatic. Conclusion: We report a case series of symptomatic chronic N2 O use, many with ongoing neurological sequelae. Furthermore, a sharp increase in Internet searches to obtain N2 O cannisters was noted. Education of high‐risk student groups on the long‐term sequelae is important.